Prevalence and associated risk factors for depression symptoms in adolescent girls with polycystic ovary syndrome: a hospital-based cross-sectional study - Wang, Lianhong; Su, Sihui; Xiong, Tingting; Wang, Meili; Ding, Rui; Tan, Huiwen; Zhu, Minglan (Frontiers in Public Health, 2024)
Background: Depression symptoms is a growing concern in adolescent girls with PCOS around the world.However relatively small samples, varying reports of its prevalence and risk factors in previous studies. Therefore it is an urgent need for further research on prevalence and associated factors of depression among adolescent girls with PCOS.. Methods: A cross-sectional study was performed from October 2021 to May 2022 using questionnaire and examination of the medical records of a convenience sample of 335 adolescent girls with PCOS. The the Chinese version of the Children's Depression Scale(CDI) was used to investigate depression symptoms. Multivariate logistic regression model was used to determine factors that were significantly associated with depression symptoms.The prevalence of depression symptoms was 36.12% among adolescents girls with PCOS.A multivariate logistic regression model identified significant factors as: perceived social support (95% CI: 0.921 0.965%, p=0.000), sleep quality (95% CI: 1.134 1.324%, p=0.000), belief illness (95% CI: 1.040 1.102%, p=0.000), hirsutism (95% CI: 1.292 4.392%, p=0.005), and LH/FSH≥2 (95% CI: 1.939 6.369%, p=0.000).Conclusions: Depression symptoms is a important problem among adolescent girls with PCOS in mainland China. A comprehensive approach that encompasses social support, structure health education for the disease, and evaluation the psychological status of PCOS girls with hirsutism (and )or LH/FSH≥2 in time, is important to minimize depression symptoms and improve psychological health among adolescent girls with PCOS.